Potential Impacts of Roe v. Wade repeal on Sexual and Reproductive Health in Sub‐Saharan Africa - Olabode Ekerin; Deborah Oluwaseun Shomuyiwa; Alex Vandy Saffa Bayoh; Ouma Sarah Atieno; Yusuf Sheku Tejan; Antor O. Ndep; Dawit Tesfagiorgis Mengesha; Mat Lowe (Wiley, 2023)
Abstract The United States (US) Supreme Court's decision to repeal Roe v. Wade has had significant implications for abortion care in the US, especially for emergency care. This ruling may also have an impact on sub‐Saharan Africa, where restrictive laws and policies limit women's access to safe and legal abortions. Sub‐Saharan Africa is the region with the highest rate of unwanted pregnancies and unsafe abortions, resulting in 15,000 preventable deaths annually. Although every country in sub‐Saharan Africa has at least one legal basis for abortion, they remain limited. In Nigeria, where 29% of pregnancies are unintended, 48% of these led to abortions, amounting to over 1.4 million abortions between 2015 and 2019. Unsafe abortions are prevalent in the region due to socioreligious stigma, particularly for unmarried women. Criminal charges can result from violating these limitations, with prison terms ranging from 3 to 14 years. The reversal of Roe v. Wade could have significant consequences in abortion‐related policies and politics in sub‐Saharan Africa, encouraging nations to adopt restrictive policies and legitimizing them. The landmark decision of Roe v. Wade may also impact the rate of unsafe abortions in the region, much like the US Mexico City Policy. With the high probability of foreign assistance funds for safe abortions depleted, sub‐Saharan African countries must prepare for this financial vacuum in health response. Therefore, the repeal of Roe v. Wade may lead to increased maternal morbidity and mortality in sub‐Saharan Africa, where access to safe and legal abortions is already limited.